### Reformatting the input :

Changes made to your input need to not affect the solution: (1): "x2" was changed by "x^2".You are watching: What value completes the square for the expression? x2 - 18x

## Step by action solution :

## Step 1 :

Trying to factor by separating the center term1.1Factoring x2-18x-63 The very first term is, x2 the coefficient is 1.The center term is, -18x the coefficient is -18.The last term, "the constant", is -63Step-1 : multiply the coefficient that the first term through the consistent 1•-63=-63Step-2 : discover two factors of -63 whose sum equates to the coefficient that the center term, i m sorry is -18.

-63 | + | 1 | = | -62 | ||

-21 | + | 3 | = | -18 | That"s it |

Step-3 : Rewrite the polynomial splitting the center term making use of the two determinants found in step2above, -21 and 3x2 - 21x+3x - 63Step-4 : add up the very first 2 terms, pulling out favor factors:x•(x-21) include up the critical 2 terms, pulling out typical factors:3•(x-21) Step-5:Add increase the 4 terms of step4:(x+3)•(x-21)Which is the desired factorization

Equation in ~ the finish of step 1 :(x + 3) • (x - 21) = 0

## Step 2 :

Theory - roots of a product :2.1 A product of number of terms equates to zero.When a product of 2 or much more terms equates to zero, then at the very least one that the terms have to be zero.We shall currently solve every term = 0 separatelyIn other words, we room going to settle as countless equations together there are terms in the productAny equipment of ax = 0 solves product = 0 as well.Solving a solitary Variable Equation:2.2Solve:x+3 = 0Subtract 3 indigenous both sides of the equation:x = -3

Solving a solitary Variable Equation:2.3Solve:x-21 = 0Add 21 come both sides of the equation:x = 21

### Supplement : resolving Quadratic Equation Directly

Solving x2-18x-63 = 0 straight Earlier we factored this polynomial by splitting the center term. Allow us now solve the equation by perfect The Square and by using the Quadratic FormulaParabola, finding the Vertex:3.1Find the vertex ofy = x2-18x-63Parabolas have actually a greatest or a lowest allude called the Vertex.Our parabola opens up up and accordingly has a lowest point (AKA pure minimum).We know this even prior to plotting "y" since the coefficient the the first term,1, is optimistic (greater 보다 zero).Each parabola has actually a vertical heat of symmetry the passes v its vertex. Thus symmetry, the heat of symmetry would, because that example, pass through the midpoint of the two x-intercepts (roots or solutions) the the parabola. That is, if the parabola has actually indeed two genuine solutions.Parabolas can model countless real life situations, such together the height over ground, of an item thrown upward, ~ some period of time. The peak of the parabola can administer us with information, such as the maximum elevation that object, thrown upwards, deserve to reach. For this reason we desire to have the ability to find the coordinates of the vertex.For any type of parabola,Ax2+Bx+C,the x-coordinate the the peak is given by -B/(2A). In our instance the x coordinate is 9.0000Plugging into the parabola formula 9.0000 for x we can calculate the y-coordinate:y = 1.0 * 9.00 * 9.00 - 18.0 * 9.00 - 63.0 or y = -144.000

Parabola, Graphing Vertex and also X-Intercepts :Root plot for : y = x2-18x-63 Axis of the contrary (dashed) x= 9.00 Vertex in ~ x,y = 9.00,-144.00 x-Intercepts (Roots) : source 1 in ~ x,y = -3.00, 0.00 source 2 at x,y = 21.00, 0.00

Solve Quadratic Equation by completing The Square3.2Solvingx2-18x-63 = 0 by perfect The Square.Add 63 to both side of the equation : x2-18x = 63Now the clever bit: take the coefficient the x, i m sorry is 18, division by two, giving 9, and finally square it providing 81Add 81 come both sides of the equation :On the appropriate hand side us have:63+81or, (63/1)+(81/1)The typical denominator the the 2 fractions is 1Adding (63/1)+(81/1) provides 144/1So including to both sides we ultimately get:x2-18x+81 = 144Adding 81 has completed the left hand side right into a perfect square :x2-18x+81=(x-9)•(x-9)=(x-9)2 things which space equal to the exact same thing are additionally equal to one another. Sincex2-18x+81 = 144 andx2-18x+81 = (x-9)2 then, according to the regulation of transitivity,(x-9)2 = 144We"ll refer to this Equation together Eq.

See more: Twist My Hips Shake It Up Lyrics, Twist My Hips Lyrics

#3.2.1 The Square source Principle says that when two things space equal, their square roots space equal.Note the the square source of(x-9)2 is(x-9)2/2=(x-9)1=x-9Now, using the Square root Principle to Eq.#3.2.1 we get:x-9= √ 144 include 9 come both sides to obtain:x = 9 + √ 144 because a square root has actually two values, one positive and also the various other negativex2 - 18x - 63 = 0has two solutions:x = 9 + √ 144 orx = 9 - √ 144

### Solve Quadratic Equation utilizing the Quadratic Formula

3.3Solvingx2-18x-63 = 0 by the Quadratic Formula.According come the Quadratic Formula,x, the equipment forAx2+Bx+C= 0 , whereby A, B and also C are numbers, often referred to as coefficients, is given by :-B± √B2-4ACx = ————————2A In our case,A= 1B=-18C=-63 Accordingly,B2-4AC=324 - (-252) = 576Applying the quadratic formula : 18 ± √ 576 x=——————2Can √ 576 be simplified ?Yes!The element factorization that 576is2•2•2•2•2•2•3•3 To have the ability to remove something from under the radical, there have to be 2 instances of that (because we room taking a square i.e. Second root).√ 576 =√2•2•2•2•2•2•3•3 =2•2•2•3•√ 1 =±24 •√ 1 =±24 So now we space looking at:x=(18±24)/2Two actual solutions:x =(18+√576)/2=9+12= 21.000 or:x =(18-√576)/2=9-12= -3.000